Histoire de l’Idjtihâd/Réformisme arabo-musulman - Aous, Rachid (Revue CMC Review, 2018)
These articles focus on the different reformist movements which have taken place from the Middle Ages to the present time on what he calls the “Quran increated”. Rachid Aous starts from the 9th century passing through the 14th and to the modern time, especially with Mohammed Arkoun. Nevertheless, he brings all of his research in the limelight of the occidental researchers such as Georges Gurvitch and Michel Foucault. And he ends to compare the paradoxes of all of these reformists.